Mashtrimi mbretëror rrëfimi për mbretin e parë dhe të fundit të Shqipërisë - Austin, Robert C. 1964- (Koha, 2024)
"Beginning in 1961, when Albanian King Zog I died in a Paris hospital after 22 years in exile, this book tells the story of this Balkan country's first and only monarch. The road to becoming Europe's youngest president in 1925 and king of Albania in 1928 was paved with feuds and assassinations, a political career-path common in the region. Zog retained his power until his "friend" Mussolini ousted him in 1939. Robert Austin holds that Zog left Albania almost as he found it, with almost no roads or trains, thoroughly uneducated and utterly impoverished. On the surface a Westernizer, the king banned the veil but achieved little else.Zog may have regretted sending a young Enver Hoxha to France on a state scholarship, where Hoxha learned some basic communist principles later used against the king. But one thing Hoxha did learn from Zog: it makes sense to have your rivals murdered. The book also describes the decades during which Hoxha practiced this lesson. The collapse of communist rule and the chaotic years of regime change saw, among other things, the miserable attempts of Zog's son Leka to revindicate his royal power.In his book, Robert Austin combines Zog's adventurous life story with a studious analysis of Albania's political history from the fall of the Ottoman Empire to the threshold of Euro-Atlantic integration"--
Keywords: Zogu -- I. -- Albanien, König -- 1895-1961; Geschichte; Politik; Albanien; Zog / I / King of the Albanians / 1895-1961; Albania / Kings and rulers / Biography; Albania / History / 1912-1944; HISTORY / Europe / Eastern